Popularizing Astronomy in the German Free Religious Movement, 1851–1852. (February 2016) - Ramberg, Peter J.
In 1851 and 1852, the Halle schoolteacher H. Weißgerber published a series of eight articles in the journal Neue Reform, zur Förderung der Religion der Menschlichkeit, a prominent journal of the German Free Religious movement. In these essays, Weißgerber took his readers on a tour of the structure and origin of the solar system and the Milky Way, but also took every opportunity to show how the results of modern astronomy made traditional religion obsolete. This essay summarizes the content of Weißgerber's articles and its relationship to the Free Religious movement, and briefly places them in the context of other works in popular astronomy in Germany and Great Britain.